The Impact of Remittances on Economic Activity : The Importance of Sectoral Linkages - Perez-Saiz, Hector (IMF Working Papers; Working Paper, 2019)
We propose a simple macroeconomic model with input-output sectoral linkages based on Acemoglu and others (2016) to quantify how changes in aggregate demand due to additional income from household's remittances propagates through the network of input-output linkages in Sub-Saharan African countries. We first propose two network centrality measures to assess the role of some sectors as key input providers in the economy. Then, we use these measures to quantify the effect of sectoral linkages on sectoral and total output following an increase in remittances inflows. Our empirical results suggest that the effects of remittances on recipient economies increase with the degree of linkages across sectors, which is especially prominent in the case of the financial intermediation sector. Our paper contributes to the emerging macroeconomic literature on the propagation of shocks across sectors and the implications for the whole economy.